In situ synthesis, crystallisation, and thin-film processing of single crystals of trans-[Ru(SO2)(NH3)4(H2O)][p-TolSO3]2 bearing SO2 linkage photo-isomers: towards optical device applications1. Issue 27 (21st July 2015) - Cole, J. M.; Yeung, K. Y. M.; Pace, G.; Sylvester, S. O.; Mersch, D.; Friend, R. H.
<x xml:space="preserve">Abstract</x> High-quality microcrystals of trans-[Ru(SO2)(NH3)4(H2O)][p-TolSO3]2 photoisomers are embedded within thin films of polyvinylacrylate, which presents opportunities for optical data storage applications.